2022
DOI: 10.1093/ofid/ofac525
|View full text |Cite
|
Sign up to set email alerts
|

A Primer on Home Infusion Administration Methods

Abstract: Home infusion therapy is a rapidly growing field in healthcare, allowing patients to receive post-acute care at home at a fraction of the cost of an inpatient stay. Understanding the various drug delivery systems can facilitate a more seamless discharge to home with improved patient outcomes. Herein we review several home infusion methods of administration utilized to transition patients from hospital to home care for a variety of therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The tubing is already attached and there is no need for gravity, which makes these devices relatively easy to use. 3 Use of elastomeric devices has been shown to be preferred by patients, 5 but this may come at the expense of a higher margin of error (15%) because flow rates depend on fluid viscosity and temperature. 4 Cost Multiple studies have demonstrated the cost-effectiveness of OPAT compared with inpatient treatment.…”
Section: Practical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tubing is already attached and there is no need for gravity, which makes these devices relatively easy to use. 3 Use of elastomeric devices has been shown to be preferred by patients, 5 but this may come at the expense of a higher margin of error (15%) because flow rates depend on fluid viscosity and temperature. 4 Cost Multiple studies have demonstrated the cost-effectiveness of OPAT compared with inpatient treatment.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…They are small enough to be worn in a small carrying case or backpack, which allows the patient to be ambulatory during the medication infusion. 3 Advantages of ambulatory infusion pumps include a lower margin of error (5%), 4 alarms that alert the patient of infusion interruption or pump malfunction, and the ability to accommodate large and varying infusion volumes. These electronic pumps are, however, more difficult for patients to use and require home care staff to be available to assist with alarms and other mechanical malfunctions.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…1 OPAT can be provided in a skilled nursing facility (SNF), long-term care or transitional care facility (LTCF), infusion therapy center (ITC), 'hospital in the home', or at home by the patient, a caregiver, or a home health nurse. 2 Standard OPAT infusion times typically range from 30 minutes to several hours. Long infusion times can be disruptive to patients' activities of daily living and decrease scheduling availability at ITCs.…”
Section: Introductionmentioning
confidence: 99%
“… 1 OPAT can be provided in a skilled nursing facility (SNF), long-term care or transitional care facility (LTCF), infusion therapy center (ITC), ‘hospital in the home’, or at home by the patient, a caregiver, or a home health nurse. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Most home infusion medications require refrigeration for stability. Therefore, the patient must remove the medication anywhere from 15–60 minutes before infusion to allow the medication to come to room temperature [ 2 ]. Coupled with the amount of time required to properly sanitize, infuse, and flush the lines, this can become cumbersome.…”
mentioning
confidence: 99%